Properties enhancement of TPNR-MWNTs-OMMT hybrid nanocomposites by using ultrasonic treatment - Tarawneh, Mou’ad A.; Sahrim Hj. Ahmad; Ku Zarina, K.A.; Ibrahim N. Hassan; Yu, Lih Jiun; Flaifel, Moayad Husein; Shamsul Bahri, A.R. (Universiti Kebangsaan Malaysia, 2013)
The main goal of this paper was to study the effect of ultrasonic treatment time on the mechanical properties of thermoplastic natural rubber (TPNR) reinforced with hybrid MWNTs-OMMT. The intercalation of TPNR enhancement into layers of clay by increasing the d-spacing was found using X-ray diffraction. The tensile properties of nanocomposites treated with ultrasonic increased when compared with untreated nanocomposites. The optimum ultrasonic treatment time was obtained at 3 h. The transmission electron microscope micrograph showed a combination of intercalated-exfoliated structure of the TPNR composites with organic clay and dispersion of MWNTs. The ultrasonic treatment can promote the dispersion of MWNTs-OMMT in TPNR and also improved the compatibility of hybrid filler and the TPNR matrix.